2011
DOI: 10.3892/mmr.2011.438
|View full text |Cite
|
Sign up to set email alerts
|

BTEB2 knockdown suppresses neointimal hyperplasia in a rat artery balloon injury model

Abstract: Abstract. Basic transcription element-binding protein 2 (BTeB2) is a regulator of the proliferation and phenotypic changes of vascular smooth muscle cells (SMcs). The aim of the present study was to determine whether or not BTeB2 knockdown inhibits balloon injury-induced neointimal hyperplasia attributed to the proliferation and phenotypic changes of vascular SMcs. We found that the knockdown of BTeB2 with antisense oligonucleotides (Ad-As-BTEB2) significantly reduced the intima/media ratio compared to uninjur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Li and colleagues [37] disclosed that the increased expression of PDGF mRNA was found on carotid artery balloon dilatation rat. Experimental results suggested that PDGF could activate its upstream pathways via directly binding PDGFR-β, which initiated intermediate signal protein, activated mitogen activated protein kinase pathway (MAPK) cascade afterwards and promoted proliferation, migration and angiogenesis in smooth muscle cells through dimerization and autophosphorylation of tyrosine residues phosphorylated [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Li and colleagues [37] disclosed that the increased expression of PDGF mRNA was found on carotid artery balloon dilatation rat. Experimental results suggested that PDGF could activate its upstream pathways via directly binding PDGFR-β, which initiated intermediate signal protein, activated mitogen activated protein kinase pathway (MAPK) cascade afterwards and promoted proliferation, migration and angiogenesis in smooth muscle cells through dimerization and autophosphorylation of tyrosine residues phosphorylated [38,39].…”
Section: Resultsmentioning
confidence: 99%